Waste management within a public organisation - Dlamini, Delly (Cranfield University, 2008)
Through air pollution from landfill, the increase in waste generation poses a local and global threat to the environment. The UK government recognises organisations’ contribution to meeting raised targets for waste recycling. This research therefore, shows that organisational waste, associated with office operations is produced in large quantities and hence, very significant in contributing towards meeting national recycling targets. The paper addresses two key areas in managing organisational office waste for sustainable development within a public organisation. First, office waste recycling logistics were examined and secondly, the link between sustainable waste management practices such as recycling and the dissemination of information to participants about waste schemes and their ultimate success was investigated. Waste policies and implementation strategies were found to be the determinants of waste management program’s effectiveness. Organisational policy and strategy were identified as drivers in mainstreaming effective waste management within an organisation, especially participation in recycling schemes and waste minimisation. Simultaneously, recycling levels and levels of waste awareness within an office showed a positive relationship. The results show that continuous waste awareness promotions are key to translating high awareness levels into action among recycling participants in the organisation. Overall, an expected reduction in waste destined for landfill was reciprocated by an increase in material collected for recycling. The implications for organisational policy making to ensure staff sustainable waste management behaviour in organisations are also explored.
Keywords: air pollution; landfill; organisational waste; recycling levels; waste management; Waste policies